The Role of Boarding School Leaders in Character Building of Santri - Nasution, Wahida Raihan; Wijaya, Candra; Fadhli, Muhammad (EDUTEC : Journal of Education And Technology, 2024)
This research examines the role of boarding school leaders in character development at the Tahfiz Quran Azhar Center Islamic Boarding School in Labuhanbatu Utara. Using a qualitative approach, the study highlights how leadership plays a critical role in shaping students' character within a comprehensive educational environment. The leaders go beyond delivering formal Islamic teachings, emphasizing values such as tolerance, cooperation, and responsibility. These values are nurtured through various methods, including lectures, role modeling, habituation, counseling, and discipline. Key internal factors, such as student motivation, and external factors, like caregiver support and quality facilities, further enhance the character-building process. Despite challenges, including student boredom and distance learning difficulties, the boarding school’s holistic approach has succeeded in fostering intellectually capable individuals who embody Islamic moral values.